Cover Picture: Porous Molybdenum Phosphide Nano‐Octahedrons Derived from Confined Phosphorization in UIO‐66 for Efficient Hydrogen Evolution (Angew. Chem. Int. Ed. 41/2016). Issue 41 (21st July 2016) - Yang, Jian; Zhang, Fengjun; Wang, Xin; He, Dongsheng; Wu, Geng; Yang, Qinghua; Hong, Xun; Wu, Yuen; Li, Yadong
Abstract : The Confinement Effect of metal–organic frameworks (MOFs) allows MoO2 nanoparticles@porous carbon to be fabricated by subliming MoO3 into the pores of the MOF UIO‐66. The resulting MoO2 nanpoarticles (NPs) were converted into MoP at 850 °C by PH3 which was generated in situ. In their Communication onpage 12854 ff. Y. Wu, Y. Li, and co‐workers show that using this strategy, MoP NPs confined in porous carbon are obtained and exhibit higher hydrogen evolution reaction (HER) activity than bulk MoP.